Does the uncovered interest parity hold in short horizons? - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2010)
In this article, one of the contemporaneous monetary theories of exchange rate determination, namely uncovered interest parity (UIP), is examined. The UIP hypothesis assumes that if capital is perfectly mobile, then investors around the world will be indifferent between holding their portfolios in domestic or foreign securities because they obtain the same return from these assets. Based on a theoretical formulation, our ex post estimation results employing four developed countries exchange rates vis-a-vis US dollar indicate the failure of the UIP hypothesis using short-horizon interest differential and future spot exchange rate data in line with most empirical papers in the economics literature.
Keywords: PREMIUM; EXCHANGE; POLICY